Management of Credit Rating Agencies – Modified “Issuer‑Pays” Model - Chodnicka-Jaworska, Patrycja (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The basic goal of the article is analyse the current regulations about credit rating agency and their activity in European Union and United States and answer the question which one the issuer or investor paid credit rating model is better, as a result building the own credit rating management model. It has been made a literature review abut actual models of risk management. Then are presented the current trends and propositions of changes in regulations. There have been described models: “issuer pays” and “investor pays” and introduced the original model management agency, taking into account the rating of four players, namely: the investor, issuer, rating agency and supervisory institutions. It has been put the following hypothesis: The introduction of regulations on credit rating agencies and credit ratings, improve the social welfare and the quality of the presented notes.